Polyhydroxyphenylvalerate/polycaprolactone nanofibers improve the life-span and mechanoresponse of human IPSC-derived cortical neuronal cells - Cerrone, Federico; Pozner, Tatyana; Siddiqui, Aarif; Ceppi, Paolo; Winner, Beate; Rajendiran, Murugan; Babu, Ramesh; Ibrahim, Hossam S.; Rodriguez, Brian J.; Winkler, Jürgen; Murphy, Keith J.; O'Connor, Kevin E. (Materials Science and Engineering C, 2020)
The physico-chemical characteristics of the extracellular matrix (ECM) cause mechanical cues that could elicit responses in the survival rate of cortical neuronal cells. Efficient neurite outgrowth in vitro, is critical for successful cultivation of cortical neuronal cells and the potential for attempts at regeneration of the central nervous system (CNS) in vivo. Relatively soft and hydrophilic, microbially synthesized aromatic polyester, polyhydroxyphenylvalerate (PHPV) was blended 50:50 with the stiff and hydrophobic polycaprolactone (PCL) and electrospun in microfibers for use in a 3D (CellCrown™) configuration and in a 2D coverslip coated configuration. This blend allows a 2.3-fold increase in the life-span of human induced pluripotent stem derived cortical neuronal cells (hiPS) compared to pure PCL fibers. HiPS-derived cortical neuronal cells grown on PHPV/PCL fibers show a 3.8-fold higher cumulative neurite elaboration compared to neurites grown on PCL fibers only. 96% of cortical neuronal cells die after 8 days of growth when plated on PCL fibers alone while >83% and 55% are alive on PHPV/PCL fibers on day 8 and day 17, respectively. An increased migration rate of cortical neuronal cells is also promoted by the blend compared to the PCL fibers alone. The critical survival rate improvement of hiPS derived cortical neuronal cells on PHPV/PCL blend holds promise in using these biocompatible nanofibers as implantable materials for regenerative purposes of an active cortical neuronal population after full maturation in vitro.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Cortical neurons; Electrospinning; HiPSC; Mechanoresponse; Neuroregeneration; Polyhydroxyalkanoates

Polyol pathway links glucose metabolism to the aggressiveness of cancer cells - Schwab, Annemarie; Siddiqui, Aarif; Vazakidou, Maria Eleni; Napoli, Francesca; Böttcher, Martin; Menchicchi, Bianca; Raza, Umar; Saatci, Ozge; Krebs, Angela; Ferrazzi, Fulvia; Rapa, Ida; Dettmer-Wilde, Katja; et al. (Cancer Research, 2018)
Cancer cells alter their metabolism to support their malignant properties. In this study, we report that the glucose-transforming polyol pathway (PP) gene aldo-keto-reductase-1-member-B1 (AKR1B1) strongly correlates with epithelial-to-mesenchymal transition (EMT). This association was confirmed in samples from lung cancer patients and from an EMT-driven colon cancer mouse model with p53 deletion. In vitro, mesenchymal-like cancer cells showed increased AKR1B1 levels, and AKR1B1 knockdown was sufficient to revert EMT. An equivalent level of EMT suppression was measured by targeting the downstream enzyme sorbitol-dehydrogenase (SORD), further pointing at the involvement of the PP. Comparative RNA sequencing confirmed a profound alteration of EMT in PP-deficient cells, revealing a strong repression of TGF-? signature genes. Excess glucose was found to promote EMT through autocrine TGF-? stimulation, while PP-deficient cells were refractory to glucose-induced EMT. These data show that PP represents a molecular link between glucose metabolism, cancer differentiation, and aggressiveness, and may serve as a novel therapeutic target.
EVALuna2:10237

The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter - Gollavilli, Paradesi Naidu; Parma, Beatrice; Siddiqui, Aarif; Yang, Hai; Ramesh, Vignesh; Napoli, Francesca; Schwab, Annemarie; Natesan, Ramakrishnan; Mielenz, Dirk; Asangani, Irfan Ahmed; Brabletz, Thomas; Pilarsky, Christian; et al. (Oncogene, 2021)
Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mesenchymal transition (EMT) as a model to show the efficacy of a fluorescent sensor to separate cells with distinct EMT signatures, based on miR-200b/c activity. The system was further combined with a CRISPR-Cas9 screening platform to unbiasedly identify miR-200b/c upstream regulating genes. The sensor allows to infer miRNAs fundamental biological properties, as profiling of sorted cells indicated miR-200b/c as a molecular switch between EMT differentiation and proliferation, and suggested a role for metabolic enzymes in miR-200/EMT regulation. Analysis of miRNAs endogenous levels and activity for in vitro and in vivo applications could lead to a better understanding of their biological role in physiology and disease.
CRIS-Team Scopus Importer:2021-03-19

Thymidylate synthase is functionally associated with ZEB1 and contributes to the epithelial-to-mesenchymal transition of cancer cells - Siddiqui, Aarif; Vazakidou, Maria Eleni; Schwab, Annemarie; Napoli, Francesca; Fernandez-Molina, Cristina; Rapa, Ida; Stemmler, Marc; Volante, Marco; Brabletz, Thomas; Ceppi, Paolo (Journal of Pathology, 2017)
Thymidylate synthase (TS) is a fundamental enzyme of nucleotide metabolism and one of the oldest anti-cancer targets. Beginning from the analysis of gene array data from the NCI-60 panel of cancer cell lines, we identified a significant correlation at both gene and protein level between TS and the markers of epithelial-to-mesenchymal transition (EMT), a developmental process that allows cancer cells to acquire features of aggressiveness, like motility and chemoresistance. TS levels were found to be significantly augmented in mesenchymal-like compared to epithelial-like cancer cells, to be regulated by EMT induction, and to negatively correlate with micro-RNAs (miRNAs) usually expressed in epithelial-like cells and known to actively suppress EMT. Transfection of EMT-suppressing miRNAs reduced TS levels, and a specific role for miR-375 in targeting the TS 3'-untranslated region was identified. A particularly relevant association was found between TS and the powerful EMT driver ZEB1, the shRNA-mediated knockdown of which up-regulated miR-375 and reduced TS cellular levels. The TS-ZEB1 association was confirmed in clinical specimens from lung tumours and in a genetic mouse model of pancreatic cancer with ZEB1 deletion. Interestingly, TS itself appeared to have a regulatory role in EMT in cancer cells, as TS knockdown could directly reduce the EMT phenotype, the migratory ability of cells, the expression of stem-like markers, and chemoresistance. Taken together, these data indicate that the TS enzyme is functionally linked with EMT and cancer differentiation, with several potential translational implications. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:10226

Thymidylate synthase maintains the de-differentiated state of triple negative breast cancers - Siddiqui, Aarif; Gollavilli, Paradesi Naidu; Schwab, Annemarie; Vazakidou, Maria Eleni; Ersan, Pelin G.; Ramakrishnan, Mallika; Pluim, Dick; Coggins, Siana A.; Saatci, Ozge; Annaratone, Laura; HM Schellens, Jan; Kim, Baek; et al. (Cell Death and Differentiation, 2019)
Cancer cells frequently boost nucleotide metabolism (NM) to support their increased proliferation, but the consequences of elevated NM on tumor de-differentiation are mostly unexplored. Here, we identified a role for thymidylate synthase (TS), a NM enzyme and established drug target, in cancer cell de-differentiation and investigated its clinical significance in breast cancer (BC). In vitro, TS knockdown increased the population of CD24 + differentiated cells, and attenuated migration and sphere-formation. RNA-seq profiling indicated repression of epithelial-to-mesenchymal transition (EMT) signature genes upon TS knockdown, and TS-deficient cells showed an increased ability to invade and metastasize in vivo, consistent with the occurrence of a partial EMT phenotype. Mechanistically, TS enzymatic activity was found essential for maintenance of the EMT/stem-like state by fueling a dihydropyrimidine dehydrogenase—dependent pyrimidine catabolism. In patient tissues, TS levels were found significantly higher in poorly differentiated and in triple negative BC, and strongly correlated with worse prognosis. The present study provides the rationale to study in-depth the role of NM at the crossroads of proliferation and differentiation, and depicts new avenues for the design of novel drug combinations for the treatment of BC.
CRIS-Team Scopus Importer:2019-08-30